A high gain EDFA using double-pass dual-stage amplification - Al-Khateeb, Khalid A. Saeed; Sellami , Ali; Belloui, Bouzid (2006)
A new configuration of an Erbium Doped Fiber Amplifier is proposed. Double-Pass amplification in a Dual-Stage using a fiber loop-back is incorporated with a Tunable Band Pass Filter. Spontaneous emission is filtered-out in the mid-section to ensure efficient amplification of the signal as it propagates along the fiber. High gain of 54dB is achieved for - 50dBm signal power at 1550nm. The two stages were pumped by laser diodes operating at 980nm with 10mW and 90mW respectively.